The Strategic Controlling Vectors of Intensification of Management of Economic Behavior of the Railway Industry Enterprises in the Conditions of Neo-Industrial Modernization - Protsenko Valentyna M. (Bìznes Inform, 2020)
The article is aimed at forming the strategic controlling vectors of intensification of management of economic behavior of the railway industry enterprises in the conditions of neo-industrial modernization. It is disclosed that the main instrument for achieving these vectors is a strategy, the choice of which is carried out in the process of strategic controlling positioning and analysis of the internal and external environment of enterprises, including, on the one hand, an evaluation of the level of economic behavior of enterprise, its resource opportunities, and, on the other hand, an evaluation of the obstacles that are formed in the market. The proposed in this article attempt to achieve the targeted strategic controlling vectors of intensification of management of economic behavior of the railway industry enterprises in the context of neo-industrial modernization is expressed within the methodological framework of the attributive concept of the general content of its properties, namely: the link to economic behavior, the desire for rationalism in the intensification of management and the results of practical actions according to the interpretation of market relations in accordance with the requirements of neo-industrial modernization, which is the basis for the efficient development of enterprises in the uncertain market conditions.